Impact of E-Business Application of Customs on Achieving Strategic Objectives: An Empirical Study on the Jordanian Customs Department - Al-A’wasa, Saleh (Jordan Journal of Business Administration, 2018)
This study aims to identify the impact of e-business customs on the strategic objectives of the Jordan Customs Department. It also investigates the extent of interaction between the Jordanian Customs Department and modern techniques in providing custom services. The study sample included all senior managers and staff of the Information and Communication Technology Directorate at the Jordanian Customs Department, whose number was 115. The researcher adopted a complete census method to examine the population of the study and a questionnaire was designed to collect data pertaining to the study’s variables. Descriptive statistics, specifically multiple regression, was used to analyze the data and to test the hypotheses of the study. The results show that there is a strong relationship between e-business customs and strategic objectives and there is a statistically significant effect of e-business customs on the strategic objectives of the Jordanian Customs Department. The study recommended paying more attention to electronic custom services, improving the relationship with customers and working to build and develop a successful strategy to stimulate e-business applications.